Income Distribution Determinants and Inequality – International Comparison - Marinko Škare; Saša Stjepanović (Amfiteatru Economic)
This study shows the relationship between income distribution and other relevant economic variables and their impact on income distribution. Panel data analysis is used to study 200 world economies and identify main income determinants. Using such a large panel to study income distribution and inequality of household income make empirical results of this study significant. Paper results show there is a large discrepancy of income distribution measured by household consumption for different classes (income deciles). Inflation, unemployment, export, labour force, population and unemployment however are the main determinants between income distribution dynamics according to the result of this study.